Incorporation of pectin during biosynthesis of bacterial cellulose by Gluconacetobacter xylinus InaCC B404: Possibility for producing green food packaging (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Agustin S, Wahyuni ET, Suparmo, Supriyadi, Cahyanto MN. 2021. Incorporation of pectin during biosynthesis of bacterial cellulose by Gluconacetobacter xylinus InaCC B404: Possibility for producing green food packaging. Biodiversitas 22: 2548-2553. Bacterial cellulose-pectin biocomposite is developed as a potential environmentally friendly food packaging material. The objective of this research was to investigate the effects of pectin supplementation to the growth medium of Gluconacetobacter xylinus on the properties of the biocomposite produced. Pectin was added into the growth medium at different concentrations, i.e.: 0.1, 0.2 and 0.3% (w/v). The bacterial cellulose-pectin biocomposites produced were analyzed for structure, mechanical strength, crystallinity, morphology, color and opacity. FTIR analysis suggested that interaction between bacterial cellulose and pectin was hydrogen bonding. Generally, pectin addition decreased the crystallinity, tensile strength, tear strength and lightness of biocomposite produced. The tensile and tear strength of bacterial cellulose-pectin biocomposites were in the range of 23.05-25.72 MPa and 13.30-15.72 g/?m respectively, comparable to those conventional non-biodegradable plastics such as high-density polyethylene and low-density polyethylene with opacity much lower than HDPE. These results suggesting the possibility of cellulose-pectin biocomposite as semi-translucent green food packaging.
Keywords: Bacterial cellulose; Gluconacetobacter xylinus; pectin